Reimagining Cape Town Walls: The Culture and Image of the City - Warries, Rosca (Department of Environmental and Geographical Science, 2020)
Public culture creates an image of the city for both local and international publics to engage and encounter. The needs of the city to be globally recognised and create opportunities for economic growth can reveal discrepancies in development agendas and raises questions about fulfilling the needs of the local public to express their understanding and selection of cultural expression. This dissertation seeks to understand the tensions in the role of street art productions in Cape Town in place making, arguing that it can run the risk of being an expression of suppression, shaped by the graffiti by-law and approval procedures. The way street art is selected, commissioned, and regulated has become an expression of culture for the global market to consume for economic development, largely through tourism as opposed to representing local cultural expressions. Previous studies of street art in Cape Town have failed to address the tension in limiting cultural producers to solely express marketable street art for tourism over the needs of social change for local publics. To identify the tensions experienced by cultural producers in producing street art in Cape Town I have examined the trade-offs of two cultural producers in becoming active participants in dominating prime locations of walls in the Cape Town central business district areas: Baz Art and Urban Khoi Soldier. Using qualitative and visual methodologies, this research explored street art in Brazil and Cape Town. The Brazilian example shows a context of unregulated expression of plural political views and citizenship within a multicultural nation. The regulation of street art in Cape Town reveals new forms of cultural colonisation where cultural representation and narratives are dominated by a globalised framework of ‘Africanity'. Therefore, this research demonstrates the lack of a variety of multicultural expressions and forms of citizenship which robs the various publics of encountering meaningful ways of seeing and being in Cape Town.